2021
DOI: 10.3390/foods10061256
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Antimicrobial Films for Food Packaging: Effect of Antimicrobials on Degradation

Abstract: The environmental problem generated by the massive consumption of plastics makes necessary the developing of biodegradable antimicrobial materials that can extend food shelf-life without having a negative impact on the environment. The current situation regarding the availability of biodegradable food packaging materials has been analysed, as well as different studies where antimicrobial compounds have been incorporated into the polymer matrix to control the growth of pathogenic or spoilage bacteria. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 100 publications
0
32
0
Order By: Relevance
“…In some of these studies [ 21 , 22 ], no changes in the film’s biodegradation behaviour were found, such as was observed when sodium propionate [ 21 ] or silicon oxide nanoparticles [ 22 ] were incorporated as antimicrobials into starch/PVA blends. Other authors showed that the effect of the antimicrobials on the biodegradation profiles of the films depended on the type and concentration of the antimicrobial compound [ 23 ]. Thus, these changes were greater when using non-volatile substances with strong antimicrobial power, such as silver species, which slowed down the degradation rate and reduced the degradation extent, suggesting a partial alteration of the compost inoculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these studies [ 21 , 22 ], no changes in the film’s biodegradation behaviour were found, such as was observed when sodium propionate [ 21 ] or silicon oxide nanoparticles [ 22 ] were incorporated as antimicrobials into starch/PVA blends. Other authors showed that the effect of the antimicrobials on the biodegradation profiles of the films depended on the type and concentration of the antimicrobial compound [ 23 ]. Thus, these changes were greater when using non-volatile substances with strong antimicrobial power, such as silver species, which slowed down the degradation rate and reduced the degradation extent, suggesting a partial alteration of the compost inoculum.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [ 9 , 24 ] also showed that the presence of catechin [ 9 ] or silver nanoparticles [ 24 ] in PHBV-based films promoted a remarkable delay in the biodegradation process. The possible changes in the biodegradation pattern of the films when incorporating antimicrobials depended on their release kinetics into the medium, the sensitivity of the different microorganisms responsible for the degradative process and the dose of active compounds in the films [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some alternatives to traditional packaging materials have been created by adding antibacterial and antioxidant substances to biopolymers (starch, cellulose, chitosan, alginate, pullulan, dairy and soy proteins and gelatin) and synthetic polymers (polyvinyl alcohol—PVA, polylactic acid—PLA, polycaprolactone—PCL) [ 3 , 4 ]. Motelica et al [ 4 ] prepared alginate-based film enriched with silver nanoparticles and lemongrass essential oil as innovative packaging for cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PVA, as a nontoxic, biocompatible, biodegradable specific synthetic polymer, can be mixed with gelatin (G) to provide a stable and resistant food packaging material [ 3 , 8 ]. In fact, some promising G/PVA blends enhanced with various additives were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Medical applications in particular, such as PCL applied in drug-delivery systems [ 2 , 3 , 4 , 5 ], medical devices using PCL for wound dressing [ 6 , 7 , 8 ], fixation devices [ 9 ] or in dentistry [ 10 , 11 ], as well as PCL included in tissue, bone, or blood vessel engineering [ 12 , 13 , 14 , 15 , 16 , 17 ], are the most investigated areas. PCL also plays an important role in the field of biodegradable and antimicrobial polymeric food packaging materials because of the increasing awareness of environmental problems with plastic waste [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%